ANALISIS PREFERENSI KONSUMEN TERHADAP PRODUK SUSU BERBASIS ANALISIS CONJOINT MENGGUNAKAN METODE PRESENTASI PAIRWISE-COMPARISON (Studi kasus di Beberapa SMP di Kecamatan Banyumanik Kota Semarang) - Trianita Resmawati; Moch. Abdul Mukid; Diah Safitri (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
In this study aims to help producer or milk companies to know and understand consumer preferences for attributes combination of milk products specifically for adolescent. The method used in this study is the conjoint analysis using pairwise-comparison as a method of presentation. In this research, the attributes that used are the type of milk, flavor, packaging, and fat content. The result of this reserach shows that the packaging is the most important attribute between the other attributes with a relative importance value of 56.13%. The second most importance attribute is flavor of milk with a relative importance value of 38.55%. Fat content was ranked in the third place with a relative importance value of 4.28%, and the type of milk as the fourth attribute with a relative importance value of 1.05%. In addition, the stimuli is desired by consumers for milk products specifically for adolescent are condensed milk, chocolate, canned, and non fat.